Targeting BRAF Activation as Acquired Resistance Mechanism to EGFR Tyrosine Kinase Inhibitors in EGFR-Mutant Non-Small-Cell Lung Cancer - Frank Aboubakar Nana (Pharmaceutics, 2021)
Osimertinib has become a standard of care in the first-line treatment of advanced-stage non-small-cell lung cancer (NSCLC) harboring exon 19 and 21 activating mutations in the EGFR gene. Nevertheless, the 18.9-month median progression-free survival emphasizes the fact that resistance to osimertinib therapy is inevitable. Acquired resistance mechanisms to osimertinib in EGFR-driven NSCLC include MET amplification, EGFR C797S mutation, neuroendocrine differentiation, small-cell lung carcinoma histologic transformation, PD-L1 and KRAS amplifications and ESR1-AKAP12 and MKRN1-BRAF translocations, as well as BRAF V600 mutation. This last one represents 3% of the acquired resistance mechanisms to osimertinib. In this review, we discuss the rationale for EGFR/BRAF/MEK co-inhibition in the light of a clinical case of EGFR-mutant NSCLC developing a BRAF V600 mutation as an acquired resistance mechanism to osimertinib and responding to the association of osimertinib plus dabrafenib and trametinib. Additionally, we discuss the acquired resistance mechanisms to osimertinib plus dabrafenib and trametinib combination in that context.